Vivendo com HIV/AIDS: estudos da ocorrência de discrimição nos serviços de saúde - Lelis, Ricardo Takeda [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Garbin, Artênio José Isper [UNESP]; Soares, Gabriella Barreto [UNESP] (My University, 2012)
Introduction: The discrimination experienced by people with HIV / AIDS, not only by society but also by health professionals is one of the major problems observed relative the epidemic. Objective: To verify and to analyze the occurrence of discriminatory attitudes in the assistance to the health of people living with HIV/AIDS. Methods: It was a quantitative research was carried out with the participation of sixty-eight HIV-positive individuals from four Brazilian cities. The participants answered auto-administrate questionnaires that contained open and closed questions including the considered subject. Results: 41.2% of the total participants, HIV + people, said they had been discriminated against by health professionals. Among the discriminatory situations experienced by HIV patients, 34.2% nursing professionals were involved, in 34.2% dentists and in 31.6% doctors were involved. Those who have suffered discrimination, 78.6% said they had been discriminated against in public health service. Conclusion: The occurrence of discrimination in the assistance to the health of HIV-positive patients was high. The majority of discrimination situations occurred in the public health service. It is necessary the institution of strategies aiming at human attendance to these patients.

Introdução: A discriminação vivenciada pelas pessoas com Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS), não apenas por parte da sociedade, mas também por profissionais de saúde, é um dos grandes problemas observado com relação à epidemia. Objetivo: Verificar e analisar a ocorrência de atitudes discriminatórias na assistência à saúde de pessoas vivendo com HIV/AIDS. Métodos: Realizou-se um estudo seccional exploratório, com a participação de 68 pessoas vivendo com HIV/AIDS em quatro municípios brasileiros. Os sujeitos da pesquisa, após consentimento livre e esclarecido, responderam a questionários autoadministrados contendo perguntas abertas e fechadas, abrangendo o tema proposto. Resultados: 41,2% do total de participantes, pessoas HIV+, afirmaram terem sido discriminadas por profissionais de saúde. Dentre as situações discriminatórias vivenciadas pelos portadores do HIV, em 34,2% estavam envolvidos os profissionais de Enfermagem, em 34,2% os cirurgiões-dentistas e em 31,6% os médicos. Das pessoas que sofreram discriminação, 78,6% afirmaram terem sido discriminadas no serviço público de saúde. Conclusão: A ocorrência de discriminação na assistência à saúde de pessoas com HIV/AIDS foi elevada, tendo acontecido em sua grande maioria no serviço público de saúde. É necessária a instituição de estratégias que visem à humanizar o atendimento a esses pacientes.
Living with HIV/AIDS: study of the occurrence of discrimination in health services
Keywords: Acquired immunodeficiency syndrome; Discrimination; Patients; HIV; Seropositivity; Bioethics; Síndrome de imunodeficiência adquirida; Discriminação; Pacientes; Soropositividade para o HIV; Bioética